2020
DOI: 10.1038/s41467-020-15906-5
|View full text |Cite
|
Sign up to set email alerts
|

Versatile whole-organ/body staining and imaging based on electrolyte-gel properties of biological tissues

Abstract: Whole-organ/body three-dimensional (3D) staining and imaging have been enduring challenges in histology. By dissecting the complex physicochemical environment of the staining system, we developed a highly optimized 3D staining imaging pipeline based on CUBIC. Based on our precise characterization of biological tissues as an electrolyte gel, we experimentally evaluated broad 3D staining conditions by using an artificial tissue-mimicking material. The combination of optimized conditions allows a bottom-up design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
210
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(213 citation statements)
references
References 61 publications
3
210
0
Order By: Relevance
“…While transgenic strategies are currently not applicable to nonhuman primates (NHP), viral approaches like RAM could be, in principle, switched to map-activated neurons in different animals (Sørensen et al, 2016). Indeed, large-scale clearing and imaging methods have been demonstrated in small NHP like the marmoset (Seiriki et al, 2017;Susaki et al, 2020). When coupled with standard neuroimaging like functional magnetic resonance imaging (fMRI) or positron-emission tomography (PET), single-cell activation mapping in NHP could provide a unique framework to better understand the relationship between neuronal activity and imaging data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While transgenic strategies are currently not applicable to nonhuman primates (NHP), viral approaches like RAM could be, in principle, switched to map-activated neurons in different animals (Sørensen et al, 2016). Indeed, large-scale clearing and imaging methods have been demonstrated in small NHP like the marmoset (Seiriki et al, 2017;Susaki et al, 2020). When coupled with standard neuroimaging like functional magnetic resonance imaging (fMRI) or positron-emission tomography (PET), single-cell activation mapping in NHP could provide a unique framework to better understand the relationship between neuronal activity and imaging data.…”
Section: Discussionmentioning
confidence: 99%
“…Anyhow, whatever optical improvement must rely on a good optical clearing, which is an essential prerequisite for the use of high-resolution LSM. The group of Hiroki Ueda has pioneered IEG mapping at subcellular resolution, demonstrating the potential of this approach to quantify neuronal activation across the entire murine brains without excluding any areas (Murakami et al, 2018;Matsumoto et al, 2019;Susaki et al, 2020).…”
Section: Imagingmentioning
confidence: 99%
“…This type of tissue is the most widely studied using tissue clearing methods ( Kim et al., 2018 ; Wan et al., 2018 ). In principle, it is essential for any method that aims at clearing neural tissue to perform a prior delipidation step to remove the myelin sheets that enclose neuronal axons ( Susaki et al., 2020 ), as their high lipidic content causes a large amount of scattering. An approach combining CLARITY with double photon microscopy enabled visualization of gray matter in the intact brain ( Chang et al., 2017 ).…”
Section: Translational Applications Of Tissue Clearing and 3d Imagingmentioning
confidence: 99%
“…CUBIC was proposed as a new brain clearing method that obviates electrophoresis, in contrast to CLARITY ( Susaki et al., 2014 ). CUBIC's clearing capability of neural tissue has been quantitatively proved by means of a small-angle X-ray scattering analysis (SAXS), which showed that CUBIC reagent 1 is capable of effectively removing the myelin sheet and, therefore, reducing scattering ( Susaki et al., 2020 ). Chicken embryo brains have been successfully cleared with an optimized CUBIC method ( Gómez-Gaviro et al., 2017 ).…”
Section: Translational Applications Of Tissue Clearing and 3d Imagingmentioning
confidence: 99%
See 1 more Smart Citation